Comparative Analysis of the Characteristics of the Social Situation of Development Primary School Children Studying in Inclusive Classes - Judina T.A (Moscow State University of Psychology and Education, 2020)
The article discusses the results of an empirical study focused on the comparative analysis of the characteristics of the social situation of development in normatively developing primary school children and children with disabilities studying in inclusive education. The study sample consisted of 14 primary school teachers and 328 students from two educational complexes in Moscow at the age from 7 to 11 years, including 18 children with a disability status , confirmed by the PMPK. The following methods were used: sociometry, the "Color Test of Relationship", criterion-oriented observation in the classroom, interviews with teachers, analysis of individual cases. Research data indicates that the social status of children with disabilities is on average lower than the social status of their normatively developing classmates. In addition, children with disabilities have a low level of self-esteem more often than their peers without disabilities. It was shown that primary school children more often demonstrate positive emotional attitude than positive social attitude, i.e. choosing as partners for joint activities, towards their classmates with disabilities.